Galactoglycerolipid Lipase PGD1 Is Involved in Thylakoid Membrane Remodeling in Response to Adverse Environmental Conditions in Chlamydomonas. Issue 2 (5th February 2018) - Du, Zhi-Yan; Lucker, Ben F.; Zienkiewicz, Krzysztof; Miller, Tarryn E.; Zienkiewicz, Agnieszka; Sears, Barbara B.; Kramer, David M.; Benning, Christoph
Abstract : The Chlamydomonas lipase PGD1 plays important roles in thylakoid lipid remodeling, thylakoid architecture, and tolerance to adverse environments. Abstract: Photosynthesis occurs in the thylakoid membrane, where the predominant lipid is monogalactosyldiacylglycerol (MGDG). As environmental conditions change, photosynthetic membranes have to adjust. In this study, we used a loss-of-function Chlamydomonas reinhardtii mutant deficient in the MGDG-specific lipase PGD1 (PLASTID GALACTOGLYCEROLIPID DEGRADATION1) to investigate the link between MGDG turnover, chloroplast ultrastructure, and the production of reactive oxygen species (ROS) in response to different adverse environmental conditions. The pgd1 mutant showed altered MGDG abundance and acyl composition and altered abundance of photosynthesis complexes, with an increased PSII/PSI ratio. Transmission electron microscopy showed hyperstacking of the thylakoid grana in the pgd1 mutant. The mutant also exhibited increased ROS production during N deprivation and high light exposure. Supplementation with bicarbonate or treatment with the photosynthetic electron transport blocker DCMU protected the cells against oxidative stress in the light and reverted chlorosis of pgd1 cells during N deprivation. Furthermore, exposure to stress conditions such as cold and high osmolarity induced the expression of PGD1, and loss of PGD1 in the mutant led to increased ROS production and inhibited cell growth. These findings suggest that PGD1 plays essential roles in maintaining appropriate thylakoid membrane composition and structure, thereby affecting growth and stress tolerance when cells are challenged under adverse conditions.